Fractionation, isolation and identification of compounds from ethyl acetate root extract of salacia macrophylla / Farah Aina Nasruddin - Nasruddin, Farah Aina (2007)
This study was carried out to study the phytochemical constituents of the ethyl acetate extracts from the roots of Salacia macrophylla. Several stages were taken in order to accomplish this study. The first stage is the fractionation of the crude extract to remove impurity that comes together with the pure compounds. Second stage was the isolation of the pure compound by thin layer chromatography. Last but not least, the pure compound that has been obtained undergoes several test methods to identify the structure of the compound by spectroscopic technique. The pure compound was identified as netzahualcoyene after comparing it to a compound that was previously isolated.